Fundamentals of the physics of solids. Volume I: Structure and dynamics - Sólyom, Jen˝o (Springer, 2012)
This ground-breaking new book is the first of a three-volume series written by the same author that plugs a real gap in the literature. It delivers a comprehensive account of the fundamentals of the physics of solids and is thus unique in the field.